Кіберспорт як сфера цивільно-правового регулювання - Харитонов, Євген Олегович; Харитонов, Є. О.; Kharytonov, Yevhen O.; Толмачевська, Юлія Олегівна; Толмачевська, Ю. О.; Tolmachevska, Yuliia O. (Одеса, 2019)
У даній статті розглядається нова, не врегульована вітчизняним законодавством сфера цивільного правового регулювання – кіберспорт. Метою даної статті є аналіз цивільно-правових відносин, які виникають у сфері кібеспорту, та пошук відповіді на питання, чи відноситься дана сфера до приватно-правової та чи необхідно здійснювати законодавче регулювання кіберспортивних відносин. На підставі одержаних результатів зроблено висновок про те, що наразі відсутні єдині підходи до правового регулювання кіберспорту, і, як наслідок, його розвиток відбувається дещо хаотично, але між тим можна спостерігати логічне запозичення деяких моделей регулювання із «традиційних» видів спорту з урахуванням специфіки кіберспортивних відносин.

This article considers a new, not regulated by national legislation sphere of civil legal regulation – eSports. The purpose of this article is to analyze the civil law relations which arise in the field of eSports and the search for an answer to the question whether this sphere is private law and whether it is necessary to carry out legislative regulation of cyber relations. It should be noted that the general foundations of eSports are similar to traditional sports: skilled players, supported by fans and sponsors, compete with each other in eTournament. Of course, the system of cyberculture has been formed, but now it is possible to isolate its constituent elements, among which are: skilled players; amateur and professional teams that take part in competitions on leading “types of cyber sport”; organizers of the event (mainly – the league); fans; videogame developers (because they create and distribute videogames that are used in cybersports); translators; and, finally, sponsors and other actors (in particular, advertisers), etc. Nevertheless, the peculiarities of cybersport through its virtual element, the means of production on the basis of intellectual property and various ways of playing should be taken into account when it comes time to draw a conclusion on the status of cybersports as a new sphere of civil law regulation. Based on the obtained results, it was concluded that today there are no common approaches to the issue of legal regulation of eSports and, therefore, its development is somewhat chaotic, but, meanwhile, one can observe the logical borrowing of some models of regulation from “traditional” sports, taking into account the specifics eSports relations.
Харитонов Є. О. Кіберспорт як сфера цивільно-правового регулювання / Є. О. Харитонов, Ю. О. Толмачевська // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Одеса, 2019. – Вип. 32. – С. 72-75.
Keywords: кіберспорт; сфера правового регулювання; приватні відносини; спортивне право; правове регулювання; eSports; legal regulation; private relations; sports law; legal regulation; Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Sports; Research Subject Categories::TECHNOLOGY